Thyroid Disrupting Chemicals - Valeria Calsolaro (International Journal of Molecular Sciences, 2017)
Endocrine disruptor compounds are exogenous agents able to interfere with a gland function, exerting their action across different functional passages, from the synthesis to the metabolism and binding to receptors of the hormone produced. Several issues, such as different levels and time of exposure and different action across different ages as well as gender, make the study of endocrine disruptors still a challenge. The thyroid is very sensitive to the action of disruptors, and considering the importance of a correct thyroid function for physical and cognitive functioning, addressing this topic should be considered a priority. In this review, we examined the most recent studies, many of them concentrating on maternal and child exposure, conducted to assess the impact of industrial chemicals which showed an influence on thyroid function. So far, the number of studies conducted on that topic is not sufficient to provide solid conclusions and lead to homogeneous guidelines. The lack of uniformity is certainly due to differences in areas and populations examined, the different conditions of exposures and the remarkable inter-subject variability. Nonetheless, the European Commission for Health and Food Safety is implementing recommendations to ensure that substances identified as endocrine disruptors will be withdrawn from the market.